Early assessment of dosimetric and biological differences of total marrow irradiation versus total body irradiation in rodents. Issue 3 (September 2017) - Hui, Susanta; Takahashi, Yutaka; Holtan, Shernan G.; Azimi, Rezvan; Seelig, Davis; Yagi, Masashi; Ingvalson, Jessie; Alaei, Parham; Sharkey, Leslie; Kodal, Behiye; Peterson, Nicholas; Meyer, Carolyn; et al.
Abstract: Purpose: To develop a murine total marrow irradiation (TMI) model in comparison with the total body irradiation (TBI) model. Materials and methods: Myeloablative TMI and TBI were administered in mice using a custom jig, and the dosimetric differences between TBI and TMI were evaluated. The early effects of TBI/TMI on bone marrow (BM) and organs were evaluated using histology, FDG-PET, and cytokine production. TMI and TBI with and without cyclophosphamide (Cy) were evaluated for donor cell engraftment and tissue damage early after allogeneic hematopoietic cell transplantation (HCT). Stromal derived factor-1 (SDF-1) expression was evaluated. Results: TMI resulted in similar dose exposure to bone and 50% reduction in dose to bystander organs. BM histology was similar between the groups. In the non-HCT model, TMI mice had significantly less acute intestinal and lung injury compared to TBI. In the HCT model, recipients of TMI had significantly less acute intestinal injury and spleen GVHD, but increased early donor cell engraftment and BM:organ SDF-1 ratio compared to TBI recipients. Conclusions: The expected BM damage was similar in both models, but the damage to other normal tissues was reduced by TMI. However, BM engraftment was improved in the TMI group compared to TBI, which may be due to enhanced production of SDF-1 in BM relative to other organs after TMI.